Membangun Pasar Tradisional yang Berdaya dan Tertata: Studi Kebijakan Penataan Pasar Mardika Kota Ambon - Djakiman, Fachrul Rozi; Kotarumalos, Amir Faisal (Populis: Jurnal Ilmu Sosial dan Ilmu Politik, 2023)
Traditional markets play a strategic role in the regional economy, serving as central hubs for community economic activities. This study aims to analyze the policy and management of Mardika Market in Ambon City to create an empowered and well-organized market. A qualitative approach with a descriptive method was employed, relying on primary and secondary data obtained through interviews, observations, and document analysis. The findings indicate that the Ambon City Government plays a role as a regulator, monitor, and motivator in managing Mardika Market. As a regulator, the government formulates policies and regulations governing market activities. As a monitor, it is responsible for overseeing traders’ compliance and market management. As a motivator, the government strives to encourage traders to enhance productivity and maintain market cleanliness. However, waste management remains a major challenge. Additionally, transparency in management and open communication between market administrators and traders are deemed essential for improving market governance effectiveness. In terms of security, the market is relatively safe, yet further improvements in orderliness and cleanliness are still necessary. This study underscores the importance of synergy between the government and traders in realizing an empowered and well-organized market. The implications of this research provide recommendations for the development of social and political sciences, particularly in public policy and traditional market management. Moreover, this study highlights the significance of a participatory approach in market management to enhance community welfare and ensure local economic sustainability.